Kualitas Laporan Keuangan Memediasi Sistem Pengendalian Internal terhadap Akuntabilitas Keuangan - Diana Santika Dewi; Endah Susilowati (IPM2KPE, 2022)
This study aims to determine the effect of the internal control system on financial accountability with the quality of financial reports as a mediating variable with a case study on the Regional Apparatus Organization (OPD) of the Jember Regency Government. This research is a quantitative research. Methods of data collection with the survey method. The data used is primary data through distributing questionnaires to respondents. The sample determined by purposive sampling method with the specified criteria is 90 respondents. The analysis technique uses the SmartPLS 3.0 application. The results showed, a) the internal control system variable on the quality of financial reports has a t statistic value of 12.345 > t table of 1.96 and a P value of 0.000 <0.05; b) the variable quality of financial reports with regard to financial accountability has a statistical t value of 5.656 > t table of 1.96 and a P Value of 0.000 <0.05; c) the internal control system variable on the quality of financial reports has a t statistic value of 2.787 > t table of 1.96 and a P Value of 0.006 <0.05. In conclusion, the internal control system contributes to the quality of financial reports, the internal control system contributes to financial accountability, financial accountability contributes to the quality of financial reports, and the quality of financial reports mediates the internal control system on financial accountability. Keywords: Financial Accountability, Quality of Financial Statements, Internal Control System